THE INFLUENCE OF ANIMATED VIDEO MEDIA ON IMPROVING OF SCIENCE LEARNING OUTCOMES (Study on Human Excretory) System) - Dian Musda Mulya Nur; Sitti Rahma Yunus; Nurhayani H. Muhiddin (Jurnal IPA Terpadu, 2024)
This study aims to determine 1) the improving of students’ learning outcomes that taught using animated video media, and who taught without using animated video media, 2) the effect using animated video media on the learning outcomes. This type research is a quasi-experimental with Non-equivalent Control Design. The population in this study were all students of class VIIIth in the academic year 2021/2022 consisting of eleven class with a total 0f 394 people, the sample was selected by purposive sampling and obtained class VIII.8 as the experimental class 36 people, and class VIII.9 as the control class 36 people. The instrument is test of learning outcomes. Data were analyzed by descriptive and inferential statistics. The result concluded: 1) the science learning outcomes of students who were taught using animated video media experienced an increase in learning outcomes with N-Gain, namely 0.38 (medium category), and who were taught without animated video experienced an increase in learning outcomes with N-Gain, namely 0,18 (low category), 2) there is an influence of the use animated video media improving student learning outcomes. Based on the test using t-test, the result obtained were 6,25(tcount) > 1,67 (ttable) so H0 was rejected and H1 accepted.